Use of MicroRNA biomarkers to distinguish enchondroma from low-grade chondrosarcoma. (4th March 2017) - Zhang, Liang; Yang, Maozhou; Mayer, Theodore; Johnstone, Brian; Les, Clifford; Frisch, Nicholas; Parsons, Theodore; Mi, Qing-Sheng; Gibson, Gary
ABSTRACT: Establishing a definitive diagnosis between benign enchondroma versus low-grade chondrosarcoma presents a potential challenge to both clinicians and pathologists. microRNAs (small non-coding RNAs) have proven to be effective biomarkers for the identification of tumors and tumor progression. We present analysis, both array and quantitative PCR, that shows consistently and substantially increased expression of two microRNAs, miRs-181a and -138, in low-grade chondrosarcomas compared with enchondromas. The data suggest these microRNAs would provide an analytical distinction between the chondrosarcoma and benign neoplasms that can be performed in formalin-fixed paraffin-embedded specimens. Together with recent publications, these data indicate that miRs-181a and -138 also play a role in tumor development and homeostasis and may provide new targets for the development of much needed therapeutic intervention.